2016
DOI: 10.1002/ejhf.626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remote monitoring on clinical outcomes and use of healthcare resources in heart failure patients with biventricular defibrillators: results of the MORE‐CARE multicentre randomized controlled trial

Abstract: NCT00885677.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(169 citation statements)
references
References 32 publications
8
153
0
8
Order By: Relevance
“…Since remote monitoring is essentially a diagnostic adjunct rather than an intervention, this may explain the lack of effect on patient outcome 67 . Similar results were obtained in two other recent studies 68 , 69 …”
Section: Telemedicine In the Management Of Heart Failure Patients To supporting
confidence: 93%
“…Since remote monitoring is essentially a diagnostic adjunct rather than an intervention, this may explain the lack of effect on patient outcome 67 . Similar results were obtained in two other recent studies 68 , 69 …”
Section: Telemedicine In the Management Of Heart Failure Patients To supporting
confidence: 93%
“…A recent meta-analysis [14] reported higher costs of standard follow-up as compared with RM mostly due a reduction in planned visits. Similar results have been observed in the MORE-CARE study [22], in which the composite endpoint of healthcare resource utilization (i.e. 2-year rates of CV hospitalizations, CV emergency department admissions, and CV in-office follow-ups), had a significant 38% reduction in the RM versus the standard arm (incidence rate ratio 0.62, 95% CI 0.58-0.66, p < 0.001) mainly driven by a reduction in in-office visits.…”
Section: Cost-effectivenesssupporting
confidence: 77%
“…The trial was terminated prematurely because of lower than expected enrollment (which predicted remarkable underpowering of the study). The analysis set included data from the 2-year follow-up [22]. …”
Section: Advances In Understanding the Effectiveness Of Rm From Recenmentioning
confidence: 99%
“…7 In all, 917 HF patients with CRT-D devices were randomized to remote and in-office device checks or the standard arm with all checks performed in the office. At a median follow-up period of 24 months, no difference between the study arms was found for the primary endpoint including all-cause death, CVD or devicerelated hospitalizations (29.7% vs. 28.7% HR 1.02, 95% CI 0.80-1.30, P=0.889) or its components.…”
Section: Andreas Gruntzig's Lecturementioning
confidence: 99%